The Effect of Vitamin D Deficiency on Anemia in Children and Adolescents: Meta-Analysis - Dianika, Bani; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: Anemia in children and adolescents has an impact on central nervous system damage that can continue into adulthood. Some evidence states that one of the causes of anemia is vitamin D deficiency. This study aims to estimate the magnitude of the effect of vitamin D deficiency on the incidence of anemia in children and adolescents, through a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: children and adolescents, intervention: vitamin D deficiency, comparison: no vitamin D deficiency, outcome: anemia. The articles used in this study were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the search key "Vitamin D" OR "25-Hydroxy Vitamin D" OR "25(OH)D" AND "Anemia" OR " Anemia". The included article is a full-text cross-sectional study design from 2010 to 2022 and reports the adjusted odds ratio (aOR) in multivariate analysis. The selection of articles is done using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.4 application. Results: A total of 9 cross-sectional studies involving 18,608 children and adolescents from the Americas and Asia were selected for meta-analysis. Children and adolescents with vitamin D deficiency had a risk of anemia 2.87 times compared to those without vitamin D deficiency (aOR= 2.87; 95% CI= 2.36 to 3.48; p<0.001). Conclusion: Vitamin D deficiency increases the risk of anemia in children and adolescents. Keywords: vitamin D deficiency, anemia, children, adolescents Correspondence:Bani Dianika. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: banidian27@gmail.com. Mobile: +62852227339349.